Pregnancy Self-Care Gaps Between First-Time and Experienced Mothers in Iraq: Kesenjangan Perawatan Mandiri Kehamilan Antara Ibu yang Baru Pertama Kali Melahirkan dan yang Sudah Berpengalaman di Irak - Fatima Shamkhi Atiyah; Sajidah Saadoon Oleiwi (Universitas Muhammadiyah Sidoarjo, 2024)
This study explores self-care behaviors among primigravida and multigravida women in Holy Karbala City, focusing on managing minor pregnancy discomforts. Amidst hormonal changes that alter the maternal body, understanding and implementing effective self-care is pivotal for pregnant women's health. This descriptive quantitative research utilized a non-probability sample of 350 women across three trimesters, analyzed using SPSS version 26. Results indicate that self-care behaviors were moderate overall and similarly moderate concerning minor discomforts. A significant correlation was found between the women's self-care behaviors and their educational level, occupation, family type, gravidity, number of abortions, parity, and length of marriage, with respective p-values of .001, .002, .004, .001, .002, .008, .050, and .011. The findings highlight the necessity of targeted educational strategies to enhance self-care practices among pregnant women, addressing demographic and reproductive characteristics that influence these behaviors. Highlights: Moderate Self-Care: Both primigravida and multigravida women displayed moderate self-care for pregnancy discomforts. Correlation with Demographics: Self-care behaviors correlate significantly with education, occupation, and family type. Need for Education: Findings suggest enhancing educational programs to improve self-care among pregnant women. Keywords: Pregnancy Self-Care, Primigravida, Multigravida, Discomfort Management